AN OPINION MINING AND SENTIMENT ANALYSIS APPROACH FOR EVALUATING CUSTOMER SATISFACTION IN A DIGITAL BANKING ENVIRONMENT - RAICU, Irina; TÜRKEȘ, Mirela Cătălina (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 18 (2016): Annales Universitatis Apulensis Series Oeconomica, 2016)
In the highly competitive digital environment, building more unique relationships with customers is vital for banking institutions. The emergence of new technologies has caused customers to reset their digital banking expectations now they have experienced personalized digital relationships in other aspects of their life. Keeping pace with digital customers is a big challenge. When building relationships with customers, satisfaction represents the foundation. Therefore, banking institutions must offer to their customers a variety of digital services and products aligned with their needs. This entails understanding customers - their perceptions, influences and motivations and how they interact with every digital banking service or product. The objective of this paper is to present an approach based on opinion mining and sentiment analysis methods on evaluating customer’s behavior in a digital banking environment.